Revealing a Mutant-Induced Receptor Allosteric Mechanism for the Thyroid Hormone Resistance - Yao, Benqiang (iScience, 2019)
Resistance to thyroid hormone (RTH) is a clinical disorder without specific and effective therapeutic strategy, partly due to the lack of structural mechanisms for the defective ligand binding by mutated thyroid hormone receptors (THRs). We herein uncovered the prescription drug roxadustat as a novel THRβ-selective ligand with therapeutic potentials in treating RTH, thereby providing a small molecule tool enabling the first probe into the structural mechanisms of RTH. Despite a wide distribution of the receptor mutation sites, different THRβ mutants induce allosteric conformational modulation on the same His435 residue, which disrupts a critical hydrogen bond required for the binding of thyroid hormones. Interestingly, roxadustat retains hydrophobic interactions with THRβ via its unique phenyl extension, enabling the rescue of the activity of the THRβ mutants. Our study thus reveals a critical receptor allosterism mechanism for RTH by mutant THRβ, providing a new and viable therapeutic strategy for the treatment of RTH.